Uncovering Global Trends in Internet of Behaviors (IoB) Research through Bibliometric Analysis - Judijanto, Loso; Husaini, Husaini; Fauzi, Fauzi; Legito, Legito; Kartini, Siti Agus (Eastasouth Institute, 2024)
The Internet of Behaviors (IoB) represents an emerging multidisciplinary field that integrates technology, data analytics, and behavioral science to influence and understand human actions through digital interactions. This study conducts a bibliometric analysis to uncover global research trends in IoB, highlighting its evolution, key themes, and emerging areas of interest. The analysis, based on publications from 2001 to 2024, reveals the central role of technological advancements such as artificial intelligence and IoT in driving IoB research. Key applications include personalized marketing, healthcare optimization, and smart city development, while ethical and privacy concerns remain critical challenges. India is identified as a leading contributor and global hub for IoB research, with significant international collaborations. Despite its rapid growth, gaps exist in understanding the long-term societal impacts of IoB and its applicability in underrepresented regions. This study emphasizes the need for interdisciplinary research, ethical governance, and inclusive collaboration to maximize IoB's potential for innovation and societal benefit.